PE ANALISIS PENGUNGKAPAN TRIPLE BOTTOM LINE DAN FAKTOR YANG MEMPENGARUHI: STUDI DI PERUSAHAAN INDONESIA DAN SINGAPURA - Yanti, Fitri; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2015)
The triple bottom line is disclosure of company's accounts that reflect overall company performance both from the economic, social, and environmental. This research was conducted at the companies listed in Singapore Stock Exchange (SGX) and Indonesia Stock Exchange( IDX) period 201 2, the number of samples taken 100 annual reports of companies. M ultiple linear regression is used as analysis techniques . P rofitabilit y, foreign ownership, and characteristic of country in this research significantly influence the disclosure by the triple bottom line of the company in Indonesia and Singapore. While leverage and liquidity does not significantly influence the triple bottom line disclosure.
Keywords: Triple bottom line, leverage, profitability, liquidity, foreign ownership, characteristic of country.